FAKTOR-FAKTOR YANG MEMPENGARUHI PEMBIAYAAN MUDHARABAH PADA PERBANKAN SYARIAH DI INDONESIA PERIODE 2010-2020 - Safhira, Sintya; Athoillah, Moh. (Islamic Economics and finance in Focus, 2023)
Mudharabah financing is a business contract based on profit sharing, where one party is the owner of the capital (shahibul maal) and the other party runs the business (mudharib). This study aims to find out how the influence of FDR, NPF, CAR, and Profit Sharing Rates on Mudharabah Financing in Islamic Commercial Banks in Indonesia for the 2010-2020 period. The data used in this research is quarterly time series data from March 2010 – December 2020. The analytical tool used in this research is multiple linear regression using quantitative methods. The results showed that the FDR variable had a significant positive effect on mudharabah financing. The NPF variable has a significant positive effect on mudharabah financing. The CAR variable has a significant positive effect on mudharabah financing. Profit sharing level variable has a significant negative effect on mudharabah financing.